Система кооперативної освіти на півдні України (1917–1929 рр.) - Shkirchak, Kateryna; Шкірчак, Катерина (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті розглянуто різноманітні форми організації кооперативної освіти для населення: кооперативні гуртки, кутки, курси, школи кооперативної грамоти, технікуми й інститути. Досліджено особливості їх функ-ціонування та фінансування. Оцінено роль указаних форм організації кооперативної освіти в справі кооперування населення та підвищення загального рівня грамотності.In the article the different forms of activity of cooperatives of south of Ukraine are examined in the field of education (cooperative corners, courses, mugs, schools of cooperative deed, technical schools, institutes). Attention applies on changes in the system of cooperative education with establishment on territory of Ukraine of new economic policy in 1921 that gave a new push to organization of network of cooperative schools. In a period from 1917-1919 cooperative education on the south of Ukraine got organized exceptionally by forces of members of cooperative in form cooperative corners and courses.
System of Cooperative Education on the South of Ukraine (1917–1929)
Keywords: кооперативна освіта; кооперативний гурток; кооперативні курси; кооперативна школа; cooperative education; cooperative group; cooperative courses; cooperative school